National Cultures of Russia in the Conditions of Society Transformation in the XXI Century. - A. L. Panishchev (Vestnik MGIMO-Universiteta)
This article is devoted to the problem of maintaining state integrity of a multicultural country – Russia – in the situations of transformations of law environment and decay of national culture. Nevertheless national culture is sole capable for keeping state integrity and civil order.